Psychological bias in the teaching of English in higher education - Rozikova Lola Tuychiyevna (Genius Journals, 2022)
This article is about the importance of psychological effects, factors and its role in language teaching; using and selecting suitable techniques in foreign language classes in order to improve learners’ communicative competences, motivation both effectively and smoothly in teaching and learning process.
Keywords: mental alertness; self-confidence; motivation; cognition